Estudo comparativo entre pavimento flexível, pavimento de concreto armado e pavimento de concreto com a implementação de barras de fibra de vidro - Silva, Nicolly Lima da (Universidade Federal de São Carlos, 2025)
Rigid, Semi-Rigid, and Flexible pavement types are used in Brazil, differing in materials, support layers, costs, design methods, and performance under various traffic conditions. The choice among them directly impacts construction and maintenance costs, influencing economic feasibility. This study presents a comparative analysis of the two most prevalent types: rigid pavement, which uses Portland cement concrete, and flexible pavement, which uses asphalt. The technical characteristics, advantages, disadvantages, and applications of both types were detailed. Additionally, the research evaluated the incorporation of glass fiber-reinforced polymer (GFRP) bars in urban concrete pavements, which act as secondary reinforcement, increasing tensile strength and allowing for a reduction in concrete thickness. This study compared flexible pavements, which use asphalt, and rigid pavements, which use Portland cement concrete. The flexible pavement had a total cost of R$139,839.47, making it the most economical option, while the rigid pavement with steel bars had a cost of R$176,913.90. The rigid pavement with glass fiber-reinforced polymer (GFRP) bars had the highest cost, R$275,696.90, but offered greater durability and corrosion resistance. Therefore, the decision to use flexible or rigid pavements should consider not only initial cost but also durability, maintenance, and road sustainability.
Comparative study between flexible pavement, reinforced concrete pavement and concrete pavement with the application of fiberglass bars
Keywords: Pavimento rígido; Pavimento flexível; Reforço de pavimento; Fibra de vidro; Gerência do pavimento; ENGENHARIAS::ENGENHARIA CIVIL::INFRA-ESTRUTURA DE TRANSPORTES